2020
DOI: 10.5114/jcb.2020.96861
|View full text |Cite
|
Sign up to set email alerts
|

Patient and physician reported toxicity with two-fraction definitive high-dose-rate prostate brachytherapy: the impact of implant interval

Abstract: Purpose: High-dose-rate (HDR) brachytherapy is an effective method of treating localized prostate cancer. There are limited data on the relationship between implant interval and outcomes. This study aims to assess if the implant interval between HDR treatments has an impact on patient-reported health-related quality of life (QOL) and physician-graded toxicity in men treated for localized prostate cancer. Material and methods: Patients were treated with HDR brachytherapy as monotherapy with 27 Gy in 2 fractions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
2
1
0
Order By: Relevance
“…Despite the lack of baseline urinary function score, given the strict patient selection for BT, 17 one would expect all men who are eligible for either LDR‐BT or HDR‐BT to have reasonably good, and likely comparable, baseline urinary function scores. Reassuringly, regardless of baseline urinary function scores, all men who had either LDR‐BT or HDR‐BT monotherapy in Victoria had excellent urinary function domain score 12‐month post‐treatment, comparable to multiple earlier series on LDR‐BT 18,19 or HDR‐BT 20–22 . The urinary function scores at 12 months after LDR‐BT or HDR‐BT monotherapy in this study were also comparable to men who had external beam radiation therapy with BT boost in previous PCOR‐Vic study 23 (Table 4).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Despite the lack of baseline urinary function score, given the strict patient selection for BT, 17 one would expect all men who are eligible for either LDR‐BT or HDR‐BT to have reasonably good, and likely comparable, baseline urinary function scores. Reassuringly, regardless of baseline urinary function scores, all men who had either LDR‐BT or HDR‐BT monotherapy in Victoria had excellent urinary function domain score 12‐month post‐treatment, comparable to multiple earlier series on LDR‐BT 18,19 or HDR‐BT 20–22 . The urinary function scores at 12 months after LDR‐BT or HDR‐BT monotherapy in this study were also comparable to men who had external beam radiation therapy with BT boost in previous PCOR‐Vic study 23 (Table 4).…”
Section: Discussionsupporting
confidence: 75%
“…Reassuringly, regardless of baseline urinary function scores, all men who had either LDR-BT or HDR-BT monotherapy in Victoria had excellent urinary function domain score 12month post-treatment, comparable to multiple earlier series on LDR-BT 18,19 or HDR-BT. [20][21][22] The urinary function scores at 12 months after LDR-BT or HDR-BT monotherapy in this study were also comparable to men who had external beam radiation therapy with BT boost in previous PCOR-Vic study 23 (Table 4). On the other hand, it is unknown whether men who had LDR-BT and HDR-BT had comparable baseline sexual function score, 24 given that pre-treatment sexual (dys)function is generally not a selection or exclusion criteria for LDR-BT or HDR-BT.…”
Section: Discussionsupporting
confidence: 63%
“…They found no differences in patient-reported health-related QoL scores or in physician-graded toxicity rates between the one-week and two-week cohorts. They concluded that HDR-BT consisting of two implants is a well-tolerated treatment for men with localized prostate cancer, and that there are no significant differences in the rates of patient-reported health-related QoL or physician-graded toxicity in patients as a function of time between each treatment [ 25 ].…”
Section: Discussionmentioning
confidence: 99%